Explainable feature selection and deep learning based emotion recognition in virtual reality using eye tracker and physiological data - Alharbi, Hadeel (Frontiers in Medicine, 2024)
Emotional recognition is a way of detecting, evaluating, interpreting, and responding to others' emotional states and feelings, which might range from delight to fear to disgrace. There is increasing interest in the domains of psychological computing and human-computer interface (HCI), especially Emotion Recognition (ER) in Virtual Reality (VR). Human emotions and mental states are effectively captured using Electroencephalography (EEG), and there has been a growing need for analysis in VR situations. In this study, we investigated emotion recognition in a VR environment using explainable machine learning and deep learning techniques. Specifically, we employed Support Vector Classifiers (SVC), K-Nearest Neighbors (KNN), Logistic Regression (LR), Deep Neural Networks (DNN), DNN with flattened layer, Bi-directional Longshort Term Memory (Bi-LSTM), and Attention LSTM. This research utilized an effective multimodal dataset named VREED (VR Eyes: Emotions Dataset) for emotion recognition. The dataset was first reduced to binary and multi-class categories. We then processed the dataset to handle missing values and applied normalization techniques to enhance data consistency. Subsequently, explainable Machine Learning (ML) and Deep Learning (DL) classifiers were employed to predict emotions in VR. Experimental analysis and results indicate that the Attention LSTM model excelled in binary classification, while both DNN and Attention LSTM achieved outstanding performance in multi-class classification, with up to 99.99% accuracy. These findings underscore the efficacy of integrating VR with advanced, explainable ML and DL methods for emotion recognition.